2017
DOI: 10.1093/mnras/stx003
|View full text |Cite
|
Sign up to set email alerts
|

Colour gradients in cluster ellipticals at z ∼ 1.4: the hidden content of the galaxy central regions

Abstract: We present F775W-F850LP (rest-frame UV-U) and F850LP-F160W (rest-frame U-R) colour gradients for a sample of 17 elliptical galaxies morphologically selected in the cluster XMMU J2235.3-2557 at z=1.39. We detected significant negative (redder inwards) U-R colour gradients in ∼70 per cent of the galaxies and flat gradients for the remaining ones. On the other hand, the UV-U gradients are significant positive (bluer inwards) for ∼80 per cent of the galaxies and flat for the remaining ones. Using stellar populatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 92 publications
0
13
0
Order By: Relevance
“…The parameters of all the galaxies in these three clusters have been homogeneously derived using Galfit on ACS-F850LP images, sampling the rest-frame B-band at the redshift of the clusters. In particular, photometry and structural parameters of galaxies have been derived and studied by Saracco et al (2014) for cluster RXJ0848, by Ciocca et al (2017) for cluster XMMJ2235 and by Saracco et al (2017) for cluster XLSS0223. Jørgensen et al (2014) find a good agreement between their measurements for cluster RXJ0848 and those by Saracco et al (2014).…”
Section: High-redshift Samplementioning
confidence: 99%
See 1 more Smart Citation
“…The parameters of all the galaxies in these three clusters have been homogeneously derived using Galfit on ACS-F850LP images, sampling the rest-frame B-band at the redshift of the clusters. In particular, photometry and structural parameters of galaxies have been derived and studied by Saracco et al (2014) for cluster RXJ0848, by Ciocca et al (2017) for cluster XMMJ2235 and by Saracco et al (2017) for cluster XLSS0223. Jørgensen et al (2014) find a good agreement between their measurements for cluster RXJ0848 and those by Saracco et al (2014).…”
Section: High-redshift Samplementioning
confidence: 99%
“…In the same Appendix, simulations dedicated to estimate the errors on the above parameters are also described, while Appendix C is dedicated to a comparison with Chan et al (2016) measurements showing a good agreement with their published measurements (see Fig. C2 of Ciocca et al 2017).…”
Section: Appendix A: High-redshift Cluster Samplementioning
confidence: 99%
“…All massive galaxies out to r ∼ 1.5 Mpc have low SFRs, and those in the centre have lower specific SFRs than the rest of the population with the same mass (Grützbauch et al 2012). For the structural properties, this cluster has been investigated by Strazzullo et al (2010) and was also included in the cluster samples of Delaye et al (2014), De Propris et al (2015) and Ciocca et al (2017).…”
Section: The Kcs Samplementioning
confidence: 99%
“…Tamura & Ohta 2003) also showed that color gradients may be preferentially produced by radial variation in metallicity rather than age. At z > 1, studies of color gradients are limited (see, for example Gargiulo et al 2012;De Propris et al 2015Ciocca et al 2017). In Chan et al (2016) we quantitatively investigated the evolution of color gradients in XMMU J2235-2557 by modeling the inner (defined to be the color at 0.5a e ) and outer (2.0a e ) regions of the galaxies under different assumptions of the radial variation of stellar population properties, using stellar population models of Bruzual & Charlot (2003).…”
Section: The Evolution Of Ratio Of Mass-weighted To Light-weighted Sizesmentioning
confidence: 99%
See 1 more Smart Citation